Factors inhibiting and enabling the implementation of inclusive education in selected South African primary schools - Ndlovu, S. M.; Makofane, I. B. (African Perspectives of Research in Teaching and Learning Journal (APORTAL), 2025)
Inclusive Education (IE) can never be emphasised enough, as it transforms schools by ensuring all learners can learn in the same space regardless of their differences. However, research suggests that rural schools across the globe are lagging, and the factors are not uniform due to varying contextual circumstances. Our study explored teachers' views on the factors that inhibit and enable the implementation of IE in rural schools. A qualitative multiple case study design and the interpretive research paradigm were adopted. Eleven teachers were purposefully selected from three primary schools. Data was collected through in-depth structured interviews and analysed using thematic data analysis. We found that the enablers of IE were workshops and informal curriculum differentiation. In contrast, unproductive workshops, overcrowded classrooms, inadequate resources, and poor parental support were inhibitors. These findings may be helpful to IE teachers and policymakers in their efforts to make primary schools inclusive. This study concludes that, regardless of the few enablers in place, IE is bound to fail in rural schools if rural teachers’ views are abeyant and there are normalised issues such as overcrowded classrooms and insufficient resources. Therefore, it is recommended that responsible education stakeholders solicit rural teachers’ views on what is working and what is not working in rural schools prior to any intervention
Journal article published in African Perspectives of Research in Teaching and Learning Journal Issue 2, Volume 9, 2025
Keywords: Inhibitors; Enablers; Inclusive education; Rural schools; Teachers; Education, Higher -- South Africa; Education, rural -- South Africa; Teachers -- South Africa; Primary school teaching